Facile one-pot synthesis of Cu-BTC metal-organic frameworks supported Keggin phosphomolybdic acid for esterification reactions. Issue 24 (17th December 2021) - Zhang, Qiuyun; Yue, Caiyan; Ao, Liufang; Lei, Dandan; Ling, Dan; Yang, Dan; Zhang, Yutao
ABSTRACT: In the present study, phosphomolybdic acid (HPMo) supported on Cu-BTC Metal-organic frameworks (MOFs) were prepared and utilized as a solid acid catalyst. The structure of the synthesized materials was characterized by using powder XRD, FT-IR, N2 adsorption-desorption, SEM, TEM, TG, and NH3 -TPD techniques. These results exposed that HPMo was successfully encapsulated in the Cu-BTC cage and the Keggin structure of HPMo was maintained in the composite catalyst. In addition, the catalytic activity and recovery properties of the HPMo/Cu-BTC catalyst for the esterification of oleic acid with methanol into biodiesel were evaluated. These results showed that the HPMo/Cu-BTC catalyst exhibited high conversion (93.7%) and excellent reusability due to its mesoporous structure, excellent acidic activity, high BET surface area, large pore volume, and good thermal stability. Meanwhile, the kinetic studies of the esterification reaction revealed that it follows pseudo-first-order kinetics with a low activation energy of 37.5 KJ/mol. More interestingly, it shows potential application for esterification of free fatty acids (FFAs) or pretreatment of low-cost feedstocks contain high FFAs content for the green production of biodiesel.